Flavor-changing neutral currents in the minimal 3-3-1 model revisited - Machado, A. C.B.; Montero, J. C. [UNESP]; Pleitez, V. [UNESP] (American Physical Society (APS), 2013)
We study a few ΔF=2 and ΔF=1 flavor-changing neutral current processes in the minimal 3-3-1 model by considering, besides the neutral vector bosons Z′, the effects due to one CP-even and one CP-odd scalar. We find that there are processes in which the interference among all the neutral bosons is constructive or destructive and in others the interference is negligible. We first obtain numerical values for all the unitary matrices that rotate the left- and right-handed quarks and give the correct mass of all the quarks in each charge sector and the Cabibbo-Kobayashi-Maskawa (CKM) mixing matrix. © 2013 American Physical Society.